Capital structure and company growth to profitability and value of manufacturing companies - Sanica, I Gede; Suidarma, I Made; Sumantri, I. GA. Alit; Ayu, Putu Cita; Marsudiana, I Dewa Nyoman (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2023)
This study aims to evaluate and analyze the impact of growth and the relationship between capital structure and company growth with profitability and company value in the context of manufacturing companies listed on the Indonesia Stock Exchange. The data used are secondary in the form of debt-to-equity ratio, return on equity, and price book value. The data is sourced from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange for 2019-2022 with a sample of 28 manufacturing companies. Data analyzed using a path analysis model is used to analyze the pattern of relationships between variables to determine the influence of the independent variable on the dependent variable. The results showed that the influence of the variable debt to equity ratio on return on equity was significant, the effect of the variable of company growth on profitability return on equity was significant, the influence of the variable capital structure debt to equity ratio to the value of the company price book value was insignificant, the influence of the variable of company growth on the value of the company was not significant, and the effect of profitability variables on company value is significant. The originality lies in the comprehensive merging of two important aspects in the management of the enterprise: factors that affect profitability and factors that affect the value of the company. It not only identifies problems and challenges that the company may face but also provides a set of concrete solutions and actions to be taken to address those problems. In addition, it emphasizes the importance of integrating financial and operational aspects in growth planning and risk management. Thus, it can create a balanced framework to help companies achieve sustainable profitability and optimal long-term value